"Because I Am Worth It": A Theoretical Framework and Empirical Review of a Justification-Based Account of Self-Regulation Failure. (May 2014) - De Witt Huberts, Jessie C.; Evers, Catharine; De Ridder, Denise T. D.
Self-regulation failure is often explained as being overwhelmed by impulse. The present article proposes a novel pathway, presenting a theoretical framework and empirical review of a justification-based account of self-regulation failure. With justification we refer to making excuses for one's discrepant behavior, so that when experiencing a self-regulation dilemma between immediate impulses and long-term intentions, people resolve the conflict by developing and employing justifications that allow violations of the goal they endorse. Accordingly, rather than inhibiting motivations from the impulsive system, the reflective system can also facilitate them, leading to self-regulation failure. We bring together empirical evidence from various domains demonstrating that justifications can instigate self-regulation failure and rule out alternative accounts. Having established that justification processes contribute to self-regulation failure, we then propose several mechanisms that may fuel the effect. Finally, routes for future research and the conceptual and practical implications of these novel insights for self-regulation are discussed.